Numerical analysis of propulsion performance of a waterjet-propelled vehicle in steady drift. (15th December 2022) - Gong, Jie; Wu, Zhongwan; Ding, Jiangming; Jiang, Jiabing; Zhang, Zhiyuan
Abstract: This paper analyzes the propulsion performance and the correlating flow details of a waterjet–propelled vehicle in straight ahead and steady turning conditions. The viscous flow field of the fully discretized waterjet – propelled vehicle is numerically solved utilizing RANS method. Drift angles ranging from 0° to 30° with an interval of 10° are considered. The theoretical control volume of waterjet system under oblique flow and the corrected thrust equation are proposed. The results show that the enhanced bilge vortex in drift alters the ingested flow pattern of the waterjet-propelled vehicle. A steady hydraulic performance of the pump is observed under non-cavitating conditions, and the inlet is one of the major source of the energy loss of the internal flow. It is problematic to evaluate the thrust and the inlet efficiency due to the irregular shape of capture area. The tangential velocity component is in proportion to the drift angle at pump inflow plane, and leads to the port/starboard asymmetry of the axial velocity and vorticity. The swirling flow rolls up near the windward inlet duct and local vortices align to the spiral axial flow. The streamwise vortex occurs and distributes near the lower-windward side of the inlet in steady turning conditions. Highlights: The theoretical control volume of waterjet system under oblique flow and the correction equation are proposed. A stable hydraulic performance of the pump is observed under steady turning maneuvering. Streamwise vortex occurs and distributes near the lower-windward side of the inlet in steady drift.